Fostering Personal and Professional Growth and Development in University Students through Internship Program - Mark Anthony Aribon III; Zandro Estella; Jessel Juniosa (Fakultas Bisnis - Institut Bio Scientia International Indonesia, 2025)
Internship program serves as an experiential learning for students to integrate theoretical and conceptual understandings into actual industry-based practice. In addition, this program allows the students to be exposed real-life experiences, experts in the field, and day-to-day transactions of an employee. This study determine the potential influence of the internship program on personal and professional development of 250 graduating students from five (5) different undergraduate degree programs who experienced the internship as a course requirement, and who were deployed to academic institutions, government agencies, business industries, and other industry partners. Using descriptive research, the findings revealed that most of the students are interested in working at their chosen company/school before internship, most of the students seek direction for better preparation for independent life and have agreed that taking their internship experience will help them land to their future job and future job promotion. Furthermore, the results demonstrate the influence of internship programs on personal and professional development, capabilities, growth and skills of the graduating students. In conclusion, this study recommends exploring the long-term impact of internship programs on personal and professional development, the factors that contribute to high-quality internship experiences, and the student's satisfaction with internship programs and identify factors that contribute to positive experiences.